On Credible Disinflation - Roldos, Jorge (IMF Working Papers; Working Paper ;, 1993)
We study the effects of a credible, gradual exchange rate based disinflation program in a two sector economy. After an initial real exchange rate depreciation, the reductions in the rate of devaluation reduce the monetary wedge generated by a cash in advance constraint, leading to a gradual increase in absorption that yields progressive real exchange rate appreciations and current account deficits. An initial boom in economic activity is not followed by a later contraction, as labor supply expands during the whole length of the program.